THE FREQUENCY OF HELICOBACTER PYLORI INFECTION IN CIRRHOTIC GASTROPATHY - Sebati ÖZDEMİR,; Hakan ŞENTÜRK,; Nagehan SEZGİÇ,; Abdullah SONSUZ,; Gülşen ÖZBAY,; Ayhan YÜCEL,; Perihan AKIN,; Muzaffer GÜRAKAR, (Turkish Journal of Gastroenterology, 2020)
-